Exercise and bone mineral accrual in children and adolescents - Burrows, M. (Journal of Sports Science & Medicine, 2007)
Osteoporosis is a serious skeletal disease causing an increase in morbidity and mortality through its association with age-related fractures. Although most effort in fracture prevention has been directed at retarding the rate of age-related bone loss and reducing the frequency and severity of trauma among elderly people, evidence is growing that peak bone mass is an important contributor to bone strength during later life. Indeed, there has been a large emphasis on the prevention of osteoporosis through the optimization of peak bone mass during childhood and adolescence. The prepubertal human skeleton is sensitive to the mechanical stimulation elicited by exercise and there is increasing evidence that regular weight-bearing exercise is an effective strategy for enhancing bone mineral throughout growth. Physical activity or participation in sports needs to start at prepubertal ages and be maintained through pubertal development to obtain the maximal peak bone mass achievable. High strain eliciting sports like gymnastics, or participation in sports or weight bearing physical activity like soccer, are strongly recommended to increase peak bone mass. Many other factors also influence the accumulation of bone mineral during childhood and adolescence, including heredity, gender, diet and endocrine status. However, this review article will focus solely on the effects of physical activity and exercise providing a summary of current knowledge on the interplay between activity, exercise and bone mass development during growth. Due to the selection bias and other confounding factors inherent in cross-sectional studies, longitudinal and intervention studies only will be reviewed for they provide a greater opportunity to examine the influence of mechanical loading on bone mineral accretion over time.